Isostructural Family of Rare‐Earth MOFs Synthesized from 1, 1, 2, 2‐Tetrakis(4‐phosphonophenyl)ethylene. Issue 34 (31st October 2022) - Steinke, Felix; Otto, Tobias; Ito, Sho; Wöhlbrandt, Stephan; Stock, Norbert
Abstract: The tetraphosphonic acid 1, 1, 2, 2‐tetrakis(4‐phosphonophenyl)ethylene (H8 L) was used as linker in the synthesis of eight new isostructural, phosphonate‐based metal‐organic frameworks of composition [M2 (H2 O)2 (H2 L)] ⋅ x H2 O (M=Y 3+, Tb 3+, Dy 3+, Ho 3+, Er 3+, Tm 3+, Yb 3+, Lu 3+ ; 1.5< x <4), denoted as M‐CAU‐34 . The compounds were synthesized under hydrothermal reaction conditions, using the corresponding metal nitrates as starting materials. The determination of the crystal structure was achieved by a combination of electron and powder X‐ray diffraction (PXRD) data. In addition, a thorough characterization by thermogravimetric and elemental analysis, IR‐ and Raman‐spectroscopy as well as H2 O‐sorption is given. Abstract : A series of porous metal phosphonates was found in hydrothermal reactions employing the linker 1, 1, 2, 2‐tetrakis(4‐phosphonophenyl)ethylene and rare‐earth nitrates. The CAU‐34 framework was obtained using rare‐earth ions with an effective ionic radius of 92–98 pm. The crystal structure of Y‐CAU‐34 was solved from electron diffraction and thoroughly characterized by PXRD, TGA, EA, MIR, Raman and sorption measurements.